2001
DOI: 10.1002/1529-0131(200106)44:6<1313::aid-art223>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum B lymphocyte stimulator levels in patients with systemic immune-based rheumatic diseases

Abstract: Objective To determine whether serum levels of B lymphocyte stimulator (BLyS) are elevated in patients with systemic immune–based rheumatic diseases and correlate with serum Ig levels and/or autoantibody titers. Methods Sera from 185 patients with various systemic immune–based rheumatic diseases (95 with systemic lupus erythematosus [SLE], 67 with rheumatoid arthritis [RA], 23 with other diagnoses) were assayed for BLyS and Ig. In 7 patients who required arthrocentesis of a swollen knee, coincident serum and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
478
3
13

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 739 publications
(527 citation statements)
references
References 29 publications
33
478
3
13
Order By: Relevance
“…It has been reported that serum BLyS protein level is more strongly correlated with autoantibodies such as anti-DNA and rheumatoid factor than with total immunoglobulin level. 24 Our present observation may support the role for BLyS in the production of autoantibodies. In addition, a patient with SLE with severe, recurrent sialoadenitis was found to be homozygous for À871T allele (data not shown).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It has been reported that serum BLyS protein level is more strongly correlated with autoantibodies such as anti-DNA and rheumatoid factor than with total immunoglobulin level. 24 Our present observation may support the role for BLyS in the production of autoantibodies. In addition, a patient with SLE with severe, recurrent sialoadenitis was found to be homozygous for À871T allele (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…4,11,22 Recently, increase of BLyS level was also reported in the serum or synovial fluid of human SLE, RA and Sjö gren's syndrome. [23][24][25] Serum BLyS level was shown to be correlated with those of anti-dsDNA antibody and rheumatoid factor (RF), 24 although another study failed to show correlation with RF or with anti-Ro, anti-La with BLyS. 25 Moreover, genome-wide screening results suggested linkage of 13q32, where the gene coding for BLyS is located, with human SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that mice over-expressing BAFF develop a lupus-like disease [72,[78][79][80]. Moreover, elevated BAFF serum levels have been found in patients with autoimmune diseases in which B cells play an important role [81,82]. Studies aimed at elucidating the mechanisms by which over expression of BAFF can result in loss of B-cell tolerance showed that BAFF over expression does not interfere with the central tolerance program in the bone marrow but rather prevents autoreactive B cells being anergized in the periphery [83].…”
mentioning
confidence: 99%
“…Cross-sectional and longitudinal studies have documented increased circulating levels of BAFF in as many as 50% of SLE patients. At the population level, circulating levels of BAFF correlate with circulating levels of anti-double-stranded DNA (anti-dsDNA) antibodies (23)(24)(25) and with clinical disease activity (26).…”
mentioning
confidence: 99%
“…Many patients with rheumatoid arthritis and Sjögren's syndrome also harbor elevated circulating levels of BAFF (23,24,27,28). Indeed, elevated circulating levels of BAFF do not necessarily result in autoimmune disease.…”
mentioning
confidence: 99%